Exofection by exosomes: A transient functional cargo transfer - Ramkumar Menon; Madhuri Tatiparthy; Jessica Selim; Isidore Mushimiyimana; Brinley Harrington; Awanit Kumar; Lauren Richardson; Emmanuel Amabebe; Ananth Kumar Kammala (Extracellular Vesicle)
Exosomes have emerged as key mediators of inter-cellular communication, transporting a diverse array of cargos that can reflect the current biological state of the cell. Recent advancements in exosome biology have unveiled their crucial role in cell signaling and paracrine-mediated functions. In this article, we will highlight the concept of exofection. In this well-defined donor-recipient relationship, donor cells produce specific biomolecules encapsulated within exosomes, which are then delivered to recipient cells. This process is particularly crucial when recipient cells experience functional deficiencies due to physiological or pathological conditions. Upon receiving the exosomal cargo, recipient cells transiently express and exhibit the functional activity of the delivered molecules. The functional enhancement mediated by exofection is transient, gradually diminishing once the delivery from the donor cells declines, and the recipient cell no longer needs specific function. Utilizing studies from various fields, we highlight the diverse biological contexts in which exofection operates. For instance, mitochondria-containing EVs from brain endothelial cells restore mitochondrial function and tight junction integrity in ischemic brain tissues. In contrast, exosomes from TNF-α-preconditioned mesenchymal stromal cells regulate autophagy and inflammation in acute pancreatitis. Similarly, Th2 cell-derived EVs promote eosinophil survival during airway inflammation, and umbilical cord blood exosomes accelerate wound healing by enhancing angiogenesis and fibroblast function. The role of exosomes in complex pathophysiological contexts such as myocardial infarction, glioblastoma, and liver failure can be crucial. In each scenario, the donor cells' exosomal cargo modulates recipient cell functions, promoting tissue repair, immune regulation, or metastasis. This work expands the conceptual framework of exofection and emphasizes its potential impact on therapeutic development and understanding the pathophysiology of various diseases.